Finding the closest efficient targets in DEA by a numeration method: the FDH non-convex technology - Vakili, Javad; Sadighidizaji, Rouhollah (Boletim da Sociedade Paranaense de Matemática, 2023)
Satisfying the Production Possibility Set (PPS) in Free Disposability Hull (FDH) property, there is only a few approaches which discuss on identifying the closest efficient targets of Decision Making Units (DMUs) in Data Envelopment Analysis (DEA). In this paper, without solving any optimization problem, a successful numeration method is proposed to compute the minimum distance of units from the strong efficient frontier of the FDH non-convex PPS. In fact, by some ratios obtained from a linear mixed-integer bi-level programming problem, the closest efficient targets of units are calculated. Moreover, there is an interesting discuss about simplifying a linear mixed-integer bi-level programming problem to reach to the ratios. Finally, the applicability of the proposed method to a real-world problem is illustrated through a numerical example